Mike Meyers' CompTIA A+ guide to managing and troubleshooting PCs lab manual (exams 220-901 & 220-902) - Meyers, Mike 1961-; Wempen, Faithe (McGraw Hill Education, 2016)
130+ Hands-On, Step-By-Step Labs, Fully Updated for the 2015 Exams T his practical workbook contains more than 130 labs that challenge you to solve real-world problems by applying key concepts. Thoroughly revised for 2015 exam objectives, the book maps directly to Mike Meyers' CompTIA A+ Guide to Managing and Troubleshooting PCs, Fifth Edition . You will get complete materials lists, setup instructions, and start-to-finish lab scenarios. "Hint" and "Warning" icons guide you through tricky situations, and post-lab questions measure your knowledge. Mike Meyers' CompTIA A+ Guide to Managing and Troubleshooting PCs Lab Manual, Fifth Edition covers: Microprocessors and Motherboards BIOS and RAM Power Supplies and Hard Drives PC Assembly Users, Groups, and Permissions Windows Vista/7/8 Virtualization OS Troubleshooting Display Technologies Local Area and WiFi Networking The Internet Mobile Device Configuration and Management Printers and Peripherals Computer Security ABOUT THE AUTHORS: Mike Meyers CompTIA A+, CompTIA Network+ ® , CompTIA Security+ ® , MCP, is the industry's leading authority on CompTIA certification and training. He is the author of eight editions of CompTIA A+ Certification All-in-One Exam Guide --the bestselling CompTIA A+ exam prep guide on the market. Faithe Wempen, M.A., CompTIA A+, has been teaching PC hardware and software architecture at Purdue University for more than a decade. She has written over 140 retail, trade, and academic books on computer applications and technologies, and her online courses for corporate clients such as CNET, Sony, and HP have educated more than a quarter of a million students.